Gestão do conhecimento nas empresas do setor metal mecânico da região da grande Santa Rosa - RS - Ternes, Antonio Roberto Lausmann (2005)
The goal of this research was to verify how the knowledge in the companies of the mechanical metal segment of Santa Rosa's area has been managed - RS and its importance as competitive diferencial. This section was chosen due to its economic importance for the area and for its growing capacity to improve the pattern of the inhabitants' life. The importance of this study is justified because once the atmosphere where these companies are inserted it is more and more complex, competitive and replete of new growth possibilities. This research possesses a theoretical grounding seeking to raise concepts and theories according to the vision of some authors and, with that, create a support for the practical development of the dissertation. Concepts linked to the administration and classification of the knowledge, creation of competitive diferencial, storage and knowledge change, technology of the information, organizational culture, intellectual capital and organizational learning are revised. Through the analysis and interpretation of the data can be verified how the culture of the information in the companies, how the information are obtained and collected. It is possible to have an accurate view on the flow of internal information and to identify how administration of the human knowledge in the companies occurs.